THE BUSH DOCTRINE FROM IRAQ TO IRAN - Ababneh, Ala Aldin Mohammad; Al Otean, Omar (جامعة آل البيت - عمادة البحث العلمي, 2014)
هدفت هذه الدراسة للوقوف على ما يسمى بنظرية بوش في نطاق القانون الدولي العام، وقد تناول البحث الحجج التي قدمت للدفاع عن المذهب، والحجج المضادة له، للوصول إلى مدى انسجام المذهب مع أحكام القانون الدولي العام، وإلى أي مدى يمكن استخدمه كذريعة قانونية للهجوم على إيران في المستقبل. وقد توصلت الدراسة إلى نتيجة مفادها أن هذا المذهب قد فارق الحياة ، وينبغي دفنه، ذلك أن الحجج التـي قدمتها الحكومة الأمريكية والتي يمكن وصفها بأنها سياسية أكثر منها قانونية لم تستطع الوقوف فـي وجـه الحجـج المضادة لهذا المذهب، وكل ذلك يقود إلى نتيجة مفادها صعوبة تصور استخدام هذا المذهب في إطار القانون الـدولي العام، كمبرر للهجوم على إيران مستقبلا. This study aims to explore the Bush Doctrine and the arguments and counter arguments used in reference to it. It further examines the extent to which this doctrine lies in harmony with international law and how it could be used as a legal ground to take action against Iran in the future. The study concludes that the Bush Doctrine no longer has any significance and should not. The arguments given by the US (which are weak and political rather than legal) have been destroyed by the counter-arguments to the Bush Doctrine. Hence, the research question for this study is, could the Bush doctrine be used in the future (particularly in the case of Iran) to preempt an attack? It was concluded that from a legal standpoint, it is difficult to envisage that these arguments could be presented again in order to attack Iran.
Keywords: القانون الدولي -- نظرية بوش -- إيران